HUMAN RELATION DALAM MENCIPTAKAN KEBERHASILAN KINERJA YANG EFISIEN - Rini Fitria (Institut Agama Islam Negeri Bengkulu, 2013)
Human relationships is the translation of human relations. There are also those who translate into